Cognitive Operations in Eco-friendly Car Advertising - Cortés de los Ríos, María Enriqueta; Negro Alousque, Isabel (International Journal of English Studies, 2022)
This paper presents a corpus-based analysis of printed eco-friendly car advertisements in English in line with the growing consumer interest in environmental issues and the development of green advertising. The aim of the research is threefold: 1) to unveil the content cognitive operations (for the purpose of this research, metonymy, metonymic chain, metaphoric amalgam and metaphor) underlying the ads and their modes of representation; 2) to examine the relationship between (i) these conceptual operations and the environmental claims made by advertisers, and (ii) the environmental claims made by advertisers and the text-image interaction. In this light, the paper yields two major findings: a) the cognitive operations underlying our corpus are usually rendered in the visual and verbal modes; b) the environmental claims underlying the ads correlate with the conceptual content and the text-image interplay. The conscious use of these mechanisms by advertisers can help the manner in which messages are interpreted.